A Study of Knowledge, Attitude and Practices Regarding Smoking among Doctors of Nishtar Hospital, Multan (Medical Forum Monthly, 2024)
Background: The World Health Organization cites Tobacco use as one of the biggest public health threats the world has ever faced. Tobacco is the number one preventable cause of disability and death. The incidence of Tobacco smoking is increasing across the globe especially amongst the youth. Since Tobacco smoking is associated with serious health problems such as Hypertension, Ischemic Heart Disease and Lung Cancer, there is an urgent need to create awareness among the masses about the health hazards and long term consequences of smoking. In Pakistan, tobacco use is common in general public and the health professionals don’t lack behind this habit.Objectives: To determine the frequency of smoking and to create awareness and health consciousness among doctors about hazards of smoking. To understand the relationship of smoking with other diseases.Study Design: Observational cross sectional studyPlace and Duration of Study: This study was conducted at Nishtar Hospital, Multan over a period of three months 15th Jan. to15th March 2012.Materials and Methods: A total of 240 male doctors,10 from each ward were selected with their informed consent. A structured questionnaire was designed. Data was collected and analyzed using EXCEL and SPSS.Results: Out of 240 doctors, 98(40.8%) were smokers and 142(59.2%) were non-smokers. Among smokers,168( 69.8%) belonged to age group 20-30 years.70( 71.4%) smokers belonged to urban areas and 28 ( 28.6%) belonged to rural areas.76(77.6%) smokers belonged to literate families and 22( 22.4%) belonged to illiterate families.38( 38.8%) smokers started smoking before joining medical school and60( 61.2%) started smoking after joining medical school. 52 (53.2%) doctors smoked 6-10 cigarettes per day. Among smokers, 44% gave positive history of smoking in friends, 34.1% gave positive smoking history of their fathers, 17.1% gave smoking history of their brothers and 4.8% about their grandfathers. Also among non-smokers, 52.2% gave positive smoking history of their friends. Within families of smokers, there was an increase frequency of hypertension (20.4%), IHD (8.2%) and lung diseases (20.4%). 40.7% doctors (smokers and non-smokers) take smoking as ‘Just a habit’, 29.6% think it as ‘A stress relief’, 14.8% as ‘Relaxation’ and 3.7% for ‘Concentration’. 49% smokers smoke outdoors and 19% smoke Indoors and 31.7% at all places. 62% smokers tried to quit smoking but among those, 73% stayed off for less than 3 months and 27% for more than 3 months.Conclusion: Most of the smoker doctors are young, from urban areas, have literate families and tell positive history of smoking in their friends. Time of start of smoking is after joining medical school. Most doctors smoke outdoors and like smoking as ‘Just a habit’ but also keeping knowledge for its ‘Health problems’. Doctors try to quit smoking but unfortunately majority of them keep themselves stay off for less than 3 months.